Enhanced lactate accumulation upregulates PD‐L1 expression to delay neutrophil apoptosis in sepsis - Miaomiao Fei; Hui Zhang; Fanbing Meng; Guanghui An; Jinxuan Tang; Jianbin Tong; Lize Xiong; Qidong Liu; Cheng Li (View, 2024)
Abstract Malfunction of neutrophil apoptosis and elevated serum lactate levels are the key cellular mechanism of immune suppressive status in septic patients. However, whether increased lactate affects apoptosis of neutrophils and aggravates sepsis development, and the molecular mechanism remain unknown. In this study, first, we analyzed the transcriptional profiles of blood cells in sepsis patients (n = 39) and healthy volunteers (n = 40) to reveal that there is close correlation between the lactate‐related gene expression changes associated with lactate production and immune function in leukocytes, especially in neutrophils. Further, we explored the close relationship between lactate and delayed neutrophil apoptosis in human neutrophils. Programmed cell death 1 legand (PD‐L1) was highly expressed in septic patients compared with healthy volunteers. Then, we indicated that elevated levels of lactate in human neutrophils decreased neutrophil apoptosis (P < .001) by upregulating PD‐L1 expression. Inhibition of monocarboxylate transporter 1 (MCT1) significantly attenuated neutrophil apoptosis caused by lactate (P < .001). We further performed in vivo experiments in sepsis mice model and determined that increased lactate decreased neutrophil apoptosis (P < .05) and reduces mice survival rate (P < .001), which could also be rescued by MCT1 inhibitor (P < .05). This study revealed that elevated level of lactate in sepsis upregulates PD‐L1 expression to decrease apoptosis through MCT1 in neutrophils, which provides new insight into sepsis treatment strategy by reducing lactate accumulation.